Characteristic of the complete chloroplast genome of L. Korolkowii Stapf, important horticultural plant in China. Issue 2 (2nd April 2020) - Ran, Hang; Zhang, Qingyuan; Zhang, Yi; Miao, Linlin; Cao, Yanan
Abstract: The genus Lonicera Linn. is among the most speciose in the Northern Hemisphere and has been important horticultural plants in China. Due to the lack of efficient molecular markers, although Lonicera has received the most extensive taxonomic evaluation historically, species discrimination within the genus is still quite difficult to this day. In this study, we characterized the complete chloroplast (cp) genome of L. korolkowii . It was 154, 664 bp in length, comprising a pair of inverted repeat (IR) regions (23, 735 bp) separated by a large single-copy (LSC) region (88, 387 bp) and a small single-copy (SSC) region (18, 745 bp). Phylogenetic analysis supported the monophyly of Caprifoliaceae, Adoxaceae and Lonicera, and suggested that Lonicera was closely related to Triosteum pinnatifidum and Heptacodium miconioides, L. korolkowii was related to L. sachalinensis. The complete cp genome of L. korolkowii will contribute to further studies on population genetics, phylogeny and conservation biology in Lonicera .